Effectiveness of Prophylactic Antibiotics in Outpatient Plastic Surgery. (November 2014) - Anigian, Kendall T.; Miller, Travis; Constantine, Ryan S.; Farkas, Jordan; Cortez, Roberto; Hein, Rachel; Lysikowski, Jerzy R.; Davis, Kathryn E.; Reed, Gary; Kenkel, Jeffrey M.
Background: The effectiveness of prophylactic antibiotics has not been established for patients who undergo plastic surgery as outpatients, and consensus guidelines for antibiotic administration in clean-contaminated plastic surgery are not available. Objectives: In a retrospective study of outpatients, the authors examined preoperative timing of prophylactic antibiotics, whether postoperative antibiotics were administered, and whether any correlations existed between these practices and surgical complications. Methods: The medical records of 468 plastic surgery outpatients were reviewed. Collected data included preoperative antibiotic timing, postoperative antibiotic use, comorbidities, and complications. Rates of complications were calculated and compared with other data. Results: All 468 patients received antibiotics preoperatively, but only 93 (19.9%) received them ≥1 hour before the initial incision. Antibiotics were administered 15 to 44 minutes before surgery in 217 patients (46.4%). There was no significant difference in complication rates between the 315 patients who received postoperative prophylactic antibiotics (16.2%) and the 153 who did not (20.9%). Comorbidities had no bearing on postoperative complications. Conclusions: Postoperative antibiotic prophylaxis may be unnecessary for outpatient plastic surgery patients. Level of Evidence: 3